Inverse Dual Converter (IDC) for High Power DC-DC Applications - Ehsani, Mehrdad; Husain, Iqbal; Bilgiç, Mehmet Oruç (IEEE, 1990)
The inverse dual converter (IDC), suitable for high-power DC-DC conversion applications, is presented. The IDC is a voltage source converter with an AC link and has been derived from an inductor converter bridge. This capacitor commutated converter is capable of continuous voltage step-up or step-down control over a wide range without the need of a transformer. In addition to high-frequency switching the converter is characterized by soft switching techniques, reducing constraints on the ratings of the switches. The average model developed with the help of gyrator theory provides sufficient information for control strategies and design considerations. The results of gyrator modeling and computer simulation are compared with experimental results obtained from a prototype IDC.
Keywords: Converter; Power; DC-DC power converters; Gyrators; Inductors; Bridge circuits; Capacitors; Voltage control; Switching converters; Switches; Computer simulation; Virtual prototyping